Answer:
The time it takes the body to cover the remaining H/4 is T
Step-by-step explanation:
The maximum height attained by the body = H
The time it takes the body to reach 3/4×H = T
From the kinematic equation, h = u·t - 1/2·g·t², we have;
u = 0 m/s at for the object returning back down at maximum height, therefore at the maximum height, we have;
H = u × 0 + 1/2·g·t²
H = 1/2·g·t²
t = √(2·H/g)
When h = 3/4×(H) from below, we have;
h = H/4 from above, which gives;
= √(2·H/4/g) = √(H/(2·g)) = 1/2 × √(2·H/g)
∴ The time it takes the body to cover H/4 height, while falling from above
= 1/2 × √(2·H/g)
The time,
, it takes to cover the remaining 3/4×(H) while falling from above is
= T = t - 1/2 × √(2·H/g) = √(2·H/g) - 1/2 × √(2·H/g) = 1/2 × √(2·H/g)
∴ T = 1/2 × √(2·H/g)
Therefore, the time it takes the body to reach a height of 3/4H = The time it takes the body to cover the remaining H/4 = T.